Nitrogen removal from wastewater using a hybrid membrane-biofilm process pilot-scale studies - Downing, Leon S (Water environment research : a research publication of the Water Environment Federation, 2010)
The hybrid membrane biofilm process (HMBP) is a new approach to achieving total nitrogen removal from wastewater. Air-filled, hollow-fiber membranes are placed into an activated sludge basin and bulk aeration is suppressed. A nitrifying biofilm develops on the membranes, exporting nitrate and nitrite to the bulk liquid. The nitrate and nitrite are reduced by suspended biomass using influent BOD as the electron donor. Previous research demonstrated the HMBP concept at the bench scale and explored process fundamentals. This research explored the HMBP at the pilot scale, with a 120-L reaction tank, real wastewater, and a potentially scalable configuration. Nitrification rates averaged 0.5 g N m(-2)/d(-1), which were lower than found at the bench scale, and lower than predicted by a mathematical model, but still allowed effluent total nitrogen concentrations below 6 mg N/L with an average influent total nitrogen concentration of 25 mg N/L and a hydraulic retention time of 12 hours. More than 75% of the produced nitrate and nitrite was reduced with an average influent sCOD of only 68 mg/L and an average C:N ratio of 3.1. Mass balances on carbon and nitrogen suggest that nitrogen removal via nitrite occurred. This research confirms that the HMBP process is effective for BOD and nitrogen removal from wastewater, and suggests that the grid configuration is viable for scale-up